2018
DOI: 10.1021/acs.orglett.8b01772
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Intramolecular Arylcyanation for the Synthesis of 3,3-Disubstituted Oxindoles

Abstract: A nickel-catalyzed arylcyanation reaction for the synthesis of 3,3-disubstituted oxindoles has been developed. This method features a bench-stable precatalyst system and serves as an economical alternative to the existing palladium-catalyzed arylcyanations described to date. A wide scope of oxindole products were accessible in moderate to good yields, and the rich chemistry of the newly installed nitrile functional group was demonstrated in the synthesis of various oxindole derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 69 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…They developed a nickel‐catalyzed arylcyanation for the synthesis of 3,3‐disubstituted oxindoles (Scheme 59). [ 129 ] A variety of heterocycles exhibited good tolerance to the reaction, providing an efficient route for applications in organic synthesis.…”
Section: Intramolecular Dicarbofunctionalization Of Alkenes Via Cyclimentioning
confidence: 99%
“…They developed a nickel‐catalyzed arylcyanation for the synthesis of 3,3‐disubstituted oxindoles (Scheme 59). [ 129 ] A variety of heterocycles exhibited good tolerance to the reaction, providing an efficient route for applications in organic synthesis.…”
Section: Intramolecular Dicarbofunctionalization Of Alkenes Via Cyclimentioning
confidence: 99%
“…Our group and others have extensively investigated the intramolecular 1,2-carbofunctionalization of olefins . Utilizing this approach, Fagnou, Zhu, and Sharma and Van der Eycken have reported trapping of the σ-Pd intermediate with activated heterocycles (Scheme a).…”
mentioning
confidence: 99%
“…35 We reported that a NiCl 2 (glyme)−DIOP catalytic system furnished cyanated oxindole products with the use of Zn(CN) 2 as the source of cyanide (Scheme 12). 36 The inclusion of activated zinc dust in the reaction mixture avoided the use of airsensitive Ni(COD) 2 , enabling the use of an easily handled NiCl 2 (glyme) precatalyst. In one substrate we observed an example of a nickel-catalyzed "chain walking" reaction, pioneered by the works of Martin and Marek, and others, 37 that generated a remotely cyanated oxindole scaffold.…”
Section: Anion-capture Cascade Reactionsmentioning
confidence: 99%